Analisis Makna dalam Mantra Bugis Masyarakat Kabupaten Soppeng (Kajian Semiotika Roland Barthes) - Tirsa Aurelia Nur Haslinda Tirsa; Abdul Kadir; Hj. A. Ebe; Kasmawati Kasmawati; Panessai Sir (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
This study aims to analyze the meanings contained in Bugis mantras of the Soppeng Regency community using Roland Barthes' semiotic approach. The method used in this study is descriptive qualitative. The data in this study consist of words and sentences of mantras found in Cabenge Village, Lilirilau District, Soppeng Regency, obtained directly from informants who are considered to have mastered mantras. The instruments used were recording devices, writing tools, and gadgets. Data collection techniques included observation, interviews, recording, note-taking, and documentation. This study employed three stages of analysis: data reduction, data presentation, and conclusion drawing. The meanings found in Bugis mantras include denotative and connotative meanings. The results show that of the 20 mantras found, 11 are denotative and 9 are connotative. This study demonstrates that mantras function not only as spiritual media but also as a means of preserving local values ​​rich in symbolic meaning.